The Transition from Acute to Chronic Pain: Might Intensive Care Unit Patients Be at Risk? - Kyranou, Maria; Puntillo, Kathleen A. (My University, 2012)
Pain remains a significant problem for patients hospitalized in intensive care units (ICUs). As research has shown, for some of these patients pain might even persist after discharge and become chronic. Exposure to intense pain and stress during medical and nursing procedures could be a risk factor that contributes to the transition from acute to chronic pain, which is a major disruption of the pain neurological system. New evidence suggests that physiological alterations contributing to chronic pain states take place both in the peripheral and central nervous systems. The purpose of this paper is to: 1) review cutting-edge theories regarding pain and mechanisms that underlie the transition from acute to chronic pain, such as increases in membrane excitability of peripheral and central nerve fibers, synaptic plasticity, and loss of the function of descending inhibitory pain fibers; 2) provide information on the association between the immune system and pain and its crucial contribution to development of chronic pain syndromes, and 3) discuss mechanisms at brain levels in the nervous system and their contribution to affective (i.e., emotional) states associated with chronic pain conditions. Finally, we will offer suggestions for ICU clinical interventions to attempt to prevent the transition from acute to chronic pain.
Keywords: Acute; Acute-to-chronic; Chronic; Critical care; Intensive care unit; Nerve sensitization; Pain